La violación de la doble conformidad en el proceso disciplinario especial de los estados de excepción - Duarte Martínez, Carlos Arturo (Derecho penal y criminología, 2024)
This article highlights the unconventionality of article 53 paragraph e of the Law 137 of 1994 that regulates disciplinary procedures. According to this provision, in cases where public servants breach their functional duties during states of emergency, the appeal of a conviction that restrict political rights is granted in the return effect. Enforcing disciplinary sanctions without first resolving the appeal is contrary to the right to double conformity and to the principle of intangibility, established in articles 8.2 paragraph h and 27.2 of the American Convention on Human Rights. This articles also proposes solutions to overcome this irregularity.